Nursing Care of Acute Pain in Rectal Cancer Patients Using Non-Pharmacological Approach with Benson Therapy: A Case Study - Olifia Nafa Jelita; Hakam, Mulia; Rondhianto; Umayanah (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Pain is the main problem experienced by many postoperative patients. One of the therapies for patients with rectal cancer is surgery, so patients with rectal cancer also feel pain after getting surgery. > 80% of patients experience postoperative pain, but appropriate pain management only occurs in approximately 30-50%. Benson's relaxation therapy reduces pain intensity in postoperative patients without causing side effects. This study aims to analyze benson therapy to reduce pain in postoperative surgery for patients with rectum cancer. The method used in this research is a descriptive case study. The research was conducted for three days on one patient with postoperative surgery in the Seruni Room at RSD dr Soebandi Jember. Benson therapy is carried out twice a day for 10-15 minutes. This study found that Benson therapy can reduce the level of acute pain in postoperative patients from the NRS scale 6 to the NRS scale 3, respiration rate 20 x/minute, SpO2 98%, blood pressure 120/80mmHg, pulse 87x/ minute. The result of reducing the pain scale indicates that Benson therapy can be applied to treat acute pain in postoperative patients to make certain patients' conditions feel better.